USING OER AS A TOOL FOR AGRIBUSINESS MANAGEMENT TRAINING FOR HARD TO REACH RURAL FARMER POPULATIONS - Muniafu, Max Maina (Online Learning, 2013)
Agriculture is the mainstay of Kenya’s economy and contributes significantly to the gross domestic product (GDP). A great majority of this comes from smallholder farmers. A major challenge is assisting these farmers to make improvements in their production ventures with an advantage that the devolved form of government in Kenya, inaugurated in 2010, has increased focus in the rural setups. United States International University (USIU) has been involved in the development of training materials for farmer organizations and specifically a course module based on several interdisciplinary field case studies was developed. This Farmers’ Agribusiness training course was developed on an Open Educational Resource (OER) platform to help both farmers (who had limited training in commercialization of agriculture) and farmer organizations. Its intention was to provide access to additional skills and knowledge to allow farmers to move from a ’farm’ to a ’firm’. Five farmers were identified from various parts of the country and were then used in partnership to develop the modules for the course over a one year period. There was frequent follow up of the farmers in field trips. There was a positive feedback on the OER materials despite challenges that the farmers must be computer literate if they were to utilize the materials directly. Mobile learning presents an opportunity to address this shortcoming. Kenya has witnessed tremendous growth in the use of mobile phones in the rural population whose main occupation is agriculture. Although a few enlightened farmers were found to have been using mobile SMS service to seek help on best agriculture practice and marketing of farm produce, there is a need to establish whether mobile technologies can enhance farmers training and support in the rural area.